Academic Coping Strategies of Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Academic coping skills are relevant in navigating the challenges and maintaining the well-being of students in a remote educational setting. Studying these skills is relevant as it equips students with strategies to cope hardships, setbacks, and academic pressures effectively. Students, notably during the pandemic, face unique academic stressors such as remote learning disruptions, social isolation, and uncertainty, emphasizing the need to address and support their coping mechanisms. Thus, this study aims to determine the academic coping strategies employed by the respondents, which yields to the creation of a proposed advocacy material for coping with academic challenges.This study employed quantitative descriptive-correlational design to describe the level to which students employ coping strategies and its relationship with their profile. The researchers gathered data from 149 Junior High School Students employed at Union Christian College during the school year 2021-2022. Frequency count and percentage was used to present their profile, weighted mean to discuss the level of use of academic coping strategies, and Pearson Product Moment Correlation for the significant relationship between the variablesThe findings show that the respondents highly approach any challenges they face in their academic engagement, particularly learning through mistakes, finding out what they did wrong, and learning from experience. Moreover, respondents moderately avoid any problems and seek social support when challenged academically. This means that respondents cope with academic challenges by engaging them as means of learning than trying to avoid it or seeking help from others. The relationship between sex and approach factor is positively and significantly related which means that female respondents tend to approach problems more than males. Furthermore, the relationship between avoidance factor and grade level is negative and significant, which means that students from higher level tend to avoid the problem than those in lower level.In online learning, students tend to learn from mistakes and experiences rather than avoiding challenges, with females more likely to actively approach problems. However, as students’ progress to higher grade levels, there's a tendency to avoid challenges, possibly due to increased pressure or confidence. The researchers recommend the adoption of a proposed advocacy material that promotes proactive approach in coping with academic challenge.
Keywords: academic challenges; coping mechanisms; academic coping strategies